2012
DOI: 10.1177/0192513x12438686
|View full text |Cite
|
Sign up to set email alerts
|

Breadwinning Moms, Caregiving Dads

Abstract: This study explores the role of gender ideologies in moderating social judgments of gender norm violators. Three hundred and eleven participants evaluated a male or a female target who was either a primary breadwinner or a primary caregiver. Attributions of personal traits, moral emotions, and marital emotions were examined. Results showed that both traditional and egalitarian individuals applied a double standard when judging deviations from gendered family roles. However, and as predicted, traditional indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 33 publications
2
31
0
7
Order By: Relevance
“…Although agentic women are often penalized in masculine occupations (e.g., Heilman, 1983), when the communal role of motherhood was made salient at work, female managers were evaluated as more likable and as more desirable supervisors and received less hostility than other women (Heilman & Okimoto, 2007). Gaunt (2013) showed that people who endorse egalitarian values viewed a breadwinning mother more favorably than a breadwinning father, consistent with the idea in RPM that one can receive benefit from engaging in nontraditional roles. These studies show that dedication to children and a spouse can buffer female workers from backlash.…”
Section: Positive Evaluations Of Women Combining Family and Workmentioning
confidence: 65%
“…Although agentic women are often penalized in masculine occupations (e.g., Heilman, 1983), when the communal role of motherhood was made salient at work, female managers were evaluated as more likable and as more desirable supervisors and received less hostility than other women (Heilman & Okimoto, 2007). Gaunt (2013) showed that people who endorse egalitarian values viewed a breadwinning mother more favorably than a breadwinning father, consistent with the idea in RPM that one can receive benefit from engaging in nontraditional roles. These studies show that dedication to children and a spouse can buffer female workers from backlash.…”
Section: Positive Evaluations Of Women Combining Family and Workmentioning
confidence: 65%
“…In the workplace, female employees are often expected to be more adroit than their male counterparts in dealing with interpersonal issues, but to perform on par with men in other life domains (Eagly, Makhijani, & Klonsky, 1992). At the same time, women's growing breadwinner role has not replaced their traditional role as caregivers, but rather has been added to their caregiving role (Gaunt, 2013;Gershuny, Bittman, & Brice, 2005). Coping flexibility may thus help women to successfully navigate their multiple social roles and deal with conflicting expectations, suggesting that this coping ability confers greater role adjustment benefits upon women than men.…”
Section: Sesmentioning
confidence: 99%
“…Such attitudes therefore not only lead men and women to seek romantic partners who conform to normative gender roles but also affect their judgments of individuals who violate these roles (Gaunt 2013a;Sakalli-Uğurlu 2010). For example, in the vocational domain it was found that hostile sexism predicted respondents' negative judgments of women studying natural sciences (Sakalli-Uğurlu 2010), women managers (Sakalli-Uğurlu and Beydogan 2002), and female candidates for masculine-typed occupational roles (Masser and Abrams 2004).…”
Section: Ambivalent Sexism Work and Family Rolesmentioning
confidence: 99%
“…Indeed, a wealth of research has established the relationships between ambivalent sexist ideologies and a vast array of preferences and attitudes toward gendered behaviors and roles (e.g., Chen et al 2009;Paynter and Leaper 2016;Russell and Trigg 2004). Nevertheless, to help maintain unequal social structures, ambivalent sexist ideologies should not just promote people's endorsement of traditional gender norms and determine their judgments of gender-norms violators (Gaunt 2013a;Sakalli-Uğurlu 2010). Rather, sexist beliefs should affect people's actual behaviors, including the work and family roles they assume.…”
mentioning
confidence: 99%